Study on TikTok as an Educational Tool: Social Media in University Motivation and Learning - Moreno Fuentes, Elena; de la Blanca de la Paz, Soledad (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The study examines the use of TikTok as an educational resource in university settings, evaluating its impact on motivation, learning, and information retention. Using a mixed-methods approach with a sample of 75 Primary Education students, the study concludes that there are no significant differences in perceptions based on gender or prior experience, highlighting the platform's inclusive nature. The qualitative analysis identifies strengths such as increased motivation, creativity, and positive emotions. The article emphasizes the importance of overcoming technical and emotional barriers to optimize its implementation, providing a foundation for future research on its educational potential.